Real-Time Lateral Predictor-Corrector Entry Guidance With Terminal Heading Angle Constraint - Shi, Peng; Xu, Jingjing; Cheng, Lin; Dong, Changhong; Huang, Xu (IEEE transactions on aerospace and electronic systems, 2025)
Predictor-corrector guidance (PCG) methods for entry flight are valued for their flexibility and adaptability. This study focuses on the lateral control of PCG with an added terminal heading angle constraint. Specifically, we propose a real-time lateral PCG algorithm that first achieves the online controllability of terminal heading angle approaching the target site. Our contributions include: 1) deriving an analytical expression for lateral trajectory prediction using a reasonably simplified entry flight model; 2) introducing a wide-range heading adjustment strategy based on the derived expression. This strategy enables online determination of the bank angle direction and reversal time, allowing for adjustment of the lateral trajectory to approach and follow the desired heading baseline; and 3) developing a discrete sliding mode guidance method to correct lateral tracking errors for subsequent lateral control, balancing reversal frequency and tracking accuracy. Combining this lateral guidance with our previously proposed deep neural networks-based longitudinal guidance method, we establish a real-time 3-D entry guidance algorithm. Simulations and Monte Carlo experiments confirm the algorithm's real-time performance, robustness, and terminal heading angle controllability.